SYSTEMIC GLUCOCORTICOID THERAPY OF RHEUMATOID ARTHRITIS AND JUVENILE RHEUMATOID ARTHRITIS - Sadikova A. M.; Ashurova D. T. (Bright Mind Publishing, 2025)
Juvenile arthritis (JA) is a chronic inflammatory joint disease that develops in children under 16 years of age. Unlike from arthritis in adults, juvenile forms have features of the course, diagnosis and treatment. The disease requires timely intervention to prevent disability, growth and quality disorders life child.